Via anti-inflamatória colinérgica e proteínas de fase aguda na tripanotolerância de coelhos infectados pelo Trypanosoma. evansi - Costa, Marcio Machado (2013)
Trypanosomiasis is a disease of worldwide distribution which in Brazil is called "mal das cadeiras", owing the clinical signs shown by horses, which are the major species affected. The disease is caused by the protozoan Trypanosoma evansi, characterized by clinical signs such as weight loss, pale mucous membranes, swelling of the eyelid and vulva. Rabbits have been reported as a resistant species to T. evansi, however, is not yet known how immune aspects, such as innate immune and cholinergic system, behave in this species, not even as this inflammations pathways influence in rabbits's trypanotolerance. Thus, the aim of this study was to investigate the inflammatory response and cholinergic anti-inflammatory pathway and its relation to trypanotolerance in rabbits infected with T. evansi. For this, twelve female adult New Zealand rabbits, weighing 3.6 4.5 kg were used in this study. The animals were divided into two groups, a control group and an infected group, both with six animals. The rabbits belonging to the infected group received, intraperitoneally, 0.5 ml of rat blood containing 108 parasites per animal, while the control group received physiological solution by the same route. The experimental period reached 118 days. Blood was collected on days 0, 2, 7, 12, 27, 42, 57, 87, 102, and 118, for to determine the cholinesterases, and days 0, 5, 20, 35, 65, 95 and 118, for to evaluate blood count, total protein, serum proteinogram, immunoglobulins and acute phase proteins. There was an increase in the activity of butyrylcholinesterase (BChE), at 7th day PI, and in the activity of acetylcholinesterase (AChE), in 27th day PI. Furthermore, the infected group showed an increase in total protein and the fractions alpha, beta and gamma globulins along of experimental period. The reduction in albumin and hematocrit were observed in precise periods of experimental infection, as well as the increase in immunoglobulin G. Infection with T. evansi stimulated the production of acute phase proteins, such as C-reactive protein, haptoglobin, α-2 macroglobulin, being observed increase in immunoglobulin M (IgM) throughout the experimental period (118 days post-infection). From these results, it is concluded that the cholinergic pathway had influence the inflammatory response, through the action of AChE and BChE in the regulation of concentrations of acetylcholine, resulting in increased concentrations of cytokines and, consequently, in the production phase protein acute. The increase in IgM, associated with increased C-reactive protein and haptoglobin, suggests the involvement of these proteins in host defense against flagellated, with possible participation in trypanotolerance of rabbits infected with T. evansi.